AS SUBNOTIFICAÇÕES DOS AGRAVOS DE SAÚDE DO TRABALHADOR NO ESTADO DE MATO GROSSO DO SUL - Eli Fernanda Brandao Lopes (2024)
Workers' health can be considered a field of knowledge and practices that aims to study, analyze and intervene in the relationship between work and illness, which has a comprehensive theoretical-methodological approach to the health-illness process and its care demands in all areas of care. Current advances in relation to Workers' Health in Primary Health Care represent the achievement of trade union movements that demanded attention from public services to workers' health problems. The integration of Occupational Health Surveillance with the other components of Health Surveillance and Primary Health Care comprises the identification and monitoring of productive activities and the profile of the working population in the assigned territory in conjunction with primary health care and the Health Surveillance sectors. The notification of health problems to workers is compulsory and is a legal requirement, through which data is provided relating to the number and distribution of accidents together with the characteristics of the occurrences and victims, generating these statistical data that constitute a fundamental basis for the indication, application and control of prevention measures. The underreporting of these diseases constitutes a limiting factor considering both the prevention and legal points of view. This work aims to identify the underreporting of nine worker health problems considered priorities by the National Workers' Health Policy in the state of Mato Grosso do Sul. To this end, it set out to understand the specific SUS policy for health of workers; to know and describe the relationship between workers' health and basic care, including the Family Health Strategy; and analyzing data on notifications of illnesses and health problems among workers in the state. This is research based on a qualitative, descriptive approach, with collection of secondary and primary data, together with data collection in the SINAN database (Notifiable Diseases Information System) at the Health Reference Center (CEREST) of Health Surveillance of the State Department of Public Health of Mato Grosso do Sul, referring to the year 2022. The findings show significant underreporting of worker health problems in the state. The results demonstrate the importance of monitoring the health of workers through primary care and, in particular, through the Family Health Strategy. Whether as a gateway to the Unified Health System (SUS), or as a point of health care in the territories of life and work, the notification of illnesses and work-related injuries, which is mandatory in all services, investigation and monitoring are very relevant for caring for people and, in particular, for promoting health in territories.